Complete Nucleotide Sequence of the IncN Plasmid Encoding IMP-6 and CTX-M-2 from Emerging Carbapenem-Resistant Enterobacteriaceae in Japan - Kayama, Shizuo (Antimicrob Agents Chemother, 2015)
We have determined the DNA sequence of Klebsiella pneumoniae multidrug resistance plasmid pKPI-6, which is a self-transmissible IncN-type plasmid. pKPI-6 harboring bla(IMP-6) and bla(CTX-M-2) confers a stealth-type carbapenem resistance phenotype on members of the family Enterobacteriaceae that is not detectable with imipenem. pKPI-6 is already epidemic in Japan, favoring the dissemination of IMP-6 and CTX-M-2 in members of the family Enterobacteriaceae.